Validation of diagnoses of liver disorders in users of systemic azole antifungal medication in Sweden - Giunta, Diego Hernan (2024)
Background Liver disorders are important adverse efects associated with antifungal drug treatment. However, the accuracy of Clinical International Classifcation of Diseases (ICD)-10 codes in identifying liver disorders for register based research is not well-established. This study aimed to determine the positive predictive value (PPV) of the ICD10 codes for identifying patients with toxic liver disease, hepatic failure, and jaundice among patients with systemic antifungal treatment. Methods Data from the Swedish Prescribed Drug Register and the National Patient Register were utilized to identify adult patients who received systemic azole antifungal drugs and had a recorded diagnosis of toxic liver disease (K71.0, K71.1, K71.2, K71.6, K71.8, K71.9), hepatic failure (K72.0, K72.9), or jaundice (R17) between 2005 and 2016. The medical records of all included patients were reviewed. Prespecifed criteria were used to re-evaluate and confrm each diagnosis, serving as the gold standard to calculate PPVs with 95% confdence intervals (95% CI) for each diagnostic group. Results Among the 115 included patients, 26 were diagnosed with toxic liver disease, 58 with hepatic failure, and 31 with jaundice. Toxic liver disease was confrmed in 14 out of 26 patients, yielding a PPV of 53.8% (95% CI 33.4–73.4%). Hepatic failure was confrmed in 26 out of 38 patients, resulting in a PPV of 62.1% (95% CI 48.4–74.5%). The highest PPV was found in jaundice, with 30 confrmed diagnoses out of 31, yielding a PPV of 96.8% (95% CI 83.3–99.9%). Conclusion Among patients who received azole antifungal treatment and were subsequently diagnosed with a liver disorder, the PPV for the diagnosis of jaundice was high, while the PPVs for toxic liver disease and hepatic failure were lower.